2016
DOI: 10.1037/bar0000027
|View full text |Cite
|
Sign up to set email alerts
|

The test-retest and interrater reliability of the Promoting the Emergence of Advanced Knowledge-Direct Training assessment for use with individuals with autism and related disabilities.

Abstract: The study evaluated the test-retest and interrater reliability of the Promoting the Emergence of Advanced Knowledge-Direct Training (PEAK-DT) assessment. In the study, the reliability of PEAK-DT scores were assessed both in terms of raw scores and age-referenced scores. To evaluate test-retest reliability, 39 participants with autism or a related disability were administered the PEAK-DT assessment on 2 occasionsduring an initial assessment and a follow-up assessment after 3 weeks to 1 month. The results sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…A second limitation was that stability in the pretest phase for the PEAK‐DTA assessment was not evaluated, as the assessment was only conducted on a single occasion for two of the participants. Repeated measures on the PEAK‐DTA were not obtained to avoid testing effects, and because the test–retest reliability of the assessment has been reported in prior research (Dixon et al, ). A final limitation was the homogeneity of the participants in the investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A second limitation was that stability in the pretest phase for the PEAK‐DTA assessment was not evaluated, as the assessment was only conducted on a single occasion for two of the participants. Repeated measures on the PEAK‐DTA were not obtained to avoid testing effects, and because the test–retest reliability of the assessment has been reported in prior research (Dixon et al, ). A final limitation was the homogeneity of the participants in the investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The topographies of operant skills across all assessment items include socially valid intervention targets (e.g., tacting community helpers, manding for preferred items), which were guided by the Common Core State Standards in the United States (National Governors Association Center for Best Practices & Council of Chief State School Officers, 2010). Research following the publication of the PEAK-DTA has supported the construct validity of the assessment Dixon, Stanley, Belisle, & Rowsey, 2016;, and correlations have been reported between the PEAK-DTA and measures of school readiness (Dixon, Carman, et al, 2014), vocabulary (McKeel, Rowsey, , and intelligence . In addition to the PEAK-DTA, PEAK-DT contains a 184-program curriculum that directly targets skills identified in the PEAK-DTA .…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Again, the Artman et al () review showed 100% of reviewed JABA studies reported IOA, and only one study in the reviewed studies reported Cohen's kappa. The same criticism also stated that no clarity exists regarding whether Dixon, Stanley, Belisle, and Rowsey () utilized Cohen's kappa to interpret IOA or IRR. Indeed, the authors explicitly stated in the article, “Interrater reliability of PEAK‐DT was assessed through Cohen's kappa” (Dixon et al, , p. 37).…”
Section: A Critical Analysis Of Witts (2018)mentioning
confidence: 99%
“…The same criticism also stated that no clarity exists regarding whether Dixon, Stanley, Belisle, and Rowsey () utilized Cohen's kappa to interpret IOA or IRR. Indeed, the authors explicitly stated in the article, “Interrater reliability of PEAK‐DT was assessed through Cohen's kappa” (Dixon et al, , p. 37). Whereas other statements Witts made could be debated as potentially untrue, this specific statement was explicitly false.…”
Section: A Critical Analysis Of Witts (2018)mentioning
confidence: 99%